Pendidikan Inklusif di Papua: Tinjauan Literatur Sosial (Lembaga Pengembangan Kinerja Dosen, 2025)
Inclusive education has become a strategic approach to addressing the challenges of unequal access and quality of education in Papua, particularly for children with special needs and other marginalized groups. This study aims to critically examine the development, challenges, and opportunities in implementing inclusive education in Papua through a social literature review. The method used is a literature study by analyzing various scholarly articles, policy reports, and official government documents published over the past two decades. The findings indicate that the implementation of inclusive education in Papua still faces numerous obstacles, including limited human resources, uneven educational infrastructure, and a lack of understanding among communities and stakeholders regarding the concept of inclusivity. Nevertheless, there are emerging local initiatives and government policies that begin to support the strengthening of inclusive education systems in the region. The implications of this study highlight the importance of collaboration between the government, communities, and educational institutions in creating an inclusive and socially just learning ecosystem in Papua.